Poorly Conserved P15 Proteins of Cileviruses Retain Elements of Common Ancestry and Putative Functionality: A Theoretical Assessment on the Evolution of Cilevirus Genomes - Ramos-González, Pedro L.; Pons, Tirso; Chabi-Jesus, Camila; Arena, Gabriella Dias; Freitas-Astua, Juliana (Frontiers in Plant Science, 2021)
The genus Cilevirus groups enveloped single-stranded (+) RNA virus members of the family Kitaviridae, order Martellivirales. Proteins P15, scarcely conserved polypeptides encoded by cileviruses, have no apparent homologs in public databases. Accordingly, the ORFs p15, located at the 5'-end of the viral RNA2 molecules, are considered orphan genes (ORFans). In this study, we have delved into ORFs p15 and the relatively poorly understood biochemical properties of the proteins P15 to posit their importance for viruses across the genus and theorize on their origin. We detected that the ORFs p15 are under purifying selection and that, in some viral strains, the use of synonymous codons is biased, which might be a sign of adaptation to their plant hosts. Despite the high amino acid sequence divergence, proteins P15 show the conserved motif [FY]-L-x(3)-[FL]-H-x-x-[LIV]-S-C-x-C-x(2)-C-x-G-x-C, which occurs exclusively in members of this protein family. Proteins P15 also show a common predicted 3D structure that resembles the helical scaffold of the protein ORF49 encoded by radinoviruses and the phosphoprotein C-terminal domain of mononegavirids. Based on the 3D structural similarities of P15, we suggest elements of common ancestry, conserved functionality, and relevant amino acid residues. We conclude by postulating a plausible evolutionary trajectory of ORFans p15 and the 5’-end of the RNA2 of cileviruses considering both protein fold superpositions and comparative genomic analyses with the closest kitaviruses, negeviruses, nege/kita-like viruses, and unrelated viruses that share the ecological niches of cileviruses.